BRCA1 Versus BRCA2 and PARP Inhibitors Efficacy in Solid Tumors:A Meta-Analysis of Randomized Controlled Trials - Li, Shan; Tao, Li; Dai, Haiyun; Gong, Xue; Zhuo, Yuguo; Xiang, Hui; Zhao, Yueyang; Gao, Qing; Deng, Liang (Frontiers in Oncology, 2021)
Abstract Background: BRCA2 mutation has a more substantial impact on the homologous recombination and superior therapeutic response to platinum-based chemotherapy than BRCA1 mutation. Whether BRCA2-mutated patients could benefit more from PARPi than BRCA1-mutated patients remains unclear. We performed a meta-analysis to assess the efficacy difference of PARPi between BRCA1 mutation carriers and BRCA2 mutation carriers. Methods: Pubmed, Embase, and Cochrane Library were comprehensively searched for randomized controlled trials (RCTs) of PARPi that had available hazard ratios (HRs) of progression-free survival (PFS) in both BRCA1-mutated population and BRCA2-mutated population. We calculated the pooled PFS HRs and 95%CI using randomized-effect models, and the difference between the two estimates was compared by interaction test. Results: A total of 11 eligible RCTs of high quality were identified through search. Overall, 1544 BRCA1 mutation carriers and 1191 BRCA2 mutation carriers were included in the final analysis. The pooled PFS HR was 0.42 (95% CI: 0.35-0.50) in BRCA1-mutated patients who were treated with PARPi compared with patients in the control group. In BRCA2-mutated patients treated with PARPi, the pooled PFS HR compared with the control groups was 0.35 (95% CI: 0.24-0.51). The difference in efficacy of PARPi was not significant between the two subgroups (Pheterogeneity = 0.40, for interaction). Conclusion: BRCA1-mutated patients and BRCA2-mutated patients could benefit from PARPi, and the efficacy is comparable. Currently, there is no evidence that BRCA2-mutated patients would benefit more from PARPi than BRCA1-mutated patients.